Radiation and checkpoint blockade immunotherapy: radiosensitisation and potential mechanisms of synergy. Issue 13 (October 2015) - Sharabi, Andrew B; Lim, Michael; DeWeese, Theodore L; Drake, Charles G
Summary: Checkpoint blockade immunotherapy has received mainstream attention as a result of striking and durable clinical responses in some patients with metastatic disease and a reasonable response rate in many tumour types. The activity of checkpoint blockade immunotherapy is not restricted to melanoma or lung cancer, and additional indications are expected in the future, with responses already reported in renal cancer, bladder cancer, and Hodgkin's lymphoma among many others. Additionally, the interactions between radiation and the immune system have been investigated, with several studies describing the synergistic effects on local and distant tumour control when radiation therapy is combined with immunotherapy. Clinical enthusiasm for this approach is strengthened by the many ongoing trials combining immunotherapy with definitive and palliative radiation. Herein, we discuss the biological and mechanistic rationale behind combining radiation with checkpoint blockade immunotherapy, with a focus on the preclinical data supporting this potentially synergistic combination. We explore potential hypotheses and important considerations for clinical trial designs. Finally, we reintroduce the notion of radiosensitising immunotherapy, akin to radiosensitising chemotherapy, as a potential definitive therapeutic modality.